(untitled) (Research, Society and Development, 2022)
Introduction: People with stroke develop in a disabling way, requiring a caregiver/family member to meet their basic needs. Objective: To analyze the scientific evidence on the main risk factors for the illness of caregivers/family members of patients with stroke. Methodology: Study carried out through an integrative review, through searches in electronic databases. The analysis was descriptive. The sample number was six scientific articles. Results: The greater the degree of dependence, the greater the physical exhaustion; emotional exhaustion and that the lack of knowledge about the comorbidity and how to care is a stressful and insecure factor for the caregiver/family member. It is evident that it is of paramount importance that upon being discharged, these caregivers/family members receive guidance to deal with the patient’s new routine. Conclusion: Negative feelings can be mitigated for these caregivers/family members with the rotation of other family members, and with the support of health professionals in patient care.